Spinoza and Spinozism in the Western Enlightenment: the Latest Turns in the Controversy - Israel, Jonathan (Araucaria, 2024)
This article seeks to outline the main elements in the historiographical controversy over the significance of ’Spinozism’ as an eighteenth-century Enlightenment category and the validity or otherwise of the concept of ’Radical Enlightenment’ as well as the relationship between these two categories. Defining ’Radical Enlightenment’ as the philosophical rejection of religious authority combined with a democratic tending system of social and political thought, and as a partly clandestine tradition that evolved in opposition to the moderate mainstream Enlightenment, it seeks to sketch in the main features both of the ’negative critique’ broadly opposing this way of understanding the Western Enlightenment and the ’positive critique’ that accepts this classification in broad outline.